Demographic and Hormonal Relationship Factors with the Incidence of Emesis Gravidarum in Pregnant Women in the First Trimester at the Sabatai Baru Health Center, Morotai Island - Hartita Sibua; Rani Safitri (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
Emesis gravidarum is a condition that is commonly experienced by pregnant women in the first trimester. This condition is characterized by complaints of nausea and vomiting which can cause discomfort, and even have the potential to cause serious complications if not handled properly. Based on data from the Sabatai Baru Health Center, Morotai Island, there were 5 cases of emesis gravidarum out of a total of 49 registered first-trimester pregnant women. Various factors, such as maternal age, parity, employment status, level of knowledge, family support, and environmental conditions, are known to play a role in the occurrence of emesis gravidarum. This study aims to examine the relationship between these factors and the incidence of emesis gravidarum in pregnant women in the first trimester at Harapan Bunda Hospital, Central Lampung. This study uses a quantitative approach with a cross-sectional design, involving 40 respondents who were selected using the total sampling technique. Data collection was carried out through questionnaires of respondent characteristics and PUQE-24 instruments, then analyzed using Chi-Square test and multivariate logistic regression. The results showed that as many as 23 respondents (57.5%) experienced mild to moderate emesis gravidarum, 17 respondents (42.5%) were in the high-risk age group, 22 respondents (55%) were primigravida, and 18 respondents (45%) had low levels of family support. Bivariate analysis showed a significant relationship between maternal age (p = 0.035), parity (p = 0.042), and family support (p = 0.001) and the incidence of emesis gravidarum. Furthermore, the results of the multivariate analysis revealed that family support was the most dominant factor influencing the occurrence of emesis gravidarum (p = 0.001; OR = 3.5). It is hoped that pregnant women will receive adequate education regarding the prevention and handling of emesis gravidarum.